Zγ production at NNLO including anomalous couplings. (November 2017) - Campbell, John; Neumann, Tobias; Williams, Ciaran
Abstract In this paper we present a next-to-next-to-leading order (NNLO) QCD calculation of the processespp →l + l − γ and pp → ν ν ¯ γ pp→ ν νγ that we have implemented in MCFM. Our calculation includes QCD corrections at NNLO both for the Standard Model (SM) and additionally in the presence ofZγγ andZZγ anomalous couplings. We compare our implementation, obtained using the jettiness slicing approach, with a previous SM calculation and find broad agreement. Focusing on the sensitivity of our results to the slicing parameter, we show that using our setup we are able to compute NNLO cross sections with numerical uncertainties of about 0.1%, which is small compared to residual scale uncertainties of a few percent. We study potential improvements using two different jettiness definitions and the inclusion of power corrections. At s = 13 s=13 TeV we present phenomenological results and considerZγ as a background toH →Zγ production. We find that, with typical cuts, the inclusion of NNLO corrections represents a small effect and loosens the extraction of limits on anomalous couplings by about 10%.